2014
DOI: 10.4161/onci.29028
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy combined withListeria monocytogenes-based cancer vaccine synergize to enhance tumor control in the B16 melanoma model

Abstract: Conceptually, the immune system may profoundly influence the efficacy of radiation therapy. Compelling evidence has recently emerged revealing the capacity of local radiation therapy (RT) to induce antitumor immune responses and sparked interest in combining RT with immunotherapy to promote tumor-specific immunity. A Listeria monocytogenes (Lm)-based cancer vaccine engineered to express tumor-associated antigen has been shown to effectively retard tumor growth by cell-mediated immune mechanisms. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The combination of Lm-based immunotherapy with radiotherapy has shown promise as a synergistic treatment regimen in a preclinical model for melanoma (86). However, there are still challenges to discover the most efficient sequence of treatment administration for both the Lm vaccine and radiotherapy, i.e.…”
Section: Listeria As a Targeted Radionuclide Therapeutic (Trt) Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of Lm-based immunotherapy with radiotherapy has shown promise as a synergistic treatment regimen in a preclinical model for melanoma (86). However, there are still challenges to discover the most efficient sequence of treatment administration for both the Lm vaccine and radiotherapy, i.e.…”
Section: Listeria As a Targeted Radionuclide Therapeutic (Trt) Platformmentioning
confidence: 99%
“…However, recent work has found that RT does not solely disrupt tumor cell division but has immunostimulatory effects in the TME (127). RT helps trigger the release of tumor antigens, improve presentation of tumor antigens to T cells, and induces an inflammatory response in the TME that results in elevated IFNg levels and reduced immunosuppression (86,128). However, despite all these attractive features of RT, resistance and recurrence still occur through multiple mechanisms (129).…”
Section: Lm In Combination With Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…42 In the B16 murine melanoma tumor model, Lim and colleagues demonstrated that local radiation therapy, followed by Lm vaccination encoding a tumor antigen, led to anti-tumor responses greater than that observed with vaccination or radiation therapy alone. 43 Finally, in clinical trials for patients with pancreatic cancer, Lm encoding a tumor antigen has been used as a booster immunization following a priming immunization with an allogeneic whole cell tumor vaccine, with evidence of clinical activity. 9 Taken together, these findings suggest that there may be a specific advantage of using Lm as a booster vaccine in prime/boost strategies.…”
Section: E1456603-6mentioning
confidence: 99%
“…Most recent studies to analyze pathological mechanisms or innovative treatments have been done on cell culture models in vitro only (1)(2)(3)(4). Preclinical in vivo animal MM models have so far been very rarely reported (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%